2015
DOI: 10.5539/gjhs.v8n3p156
|View full text |Cite
|
Sign up to set email alerts
|

Self Management Behaviors in Rheumatoid Arthritis Patients and Associated Factors in Tehran 2013

Abstract: Introduction:Rheumatoid Arthritis (RA) is a systemic, autoimmune and inflammatory disease with an unknown etiology that is associated with progressive joint degeneration, limitation of physical activity and disability. The aim of the study was to evaluate self-management behaviors and their associated factors in RA patients.Material and Method:This cross-sectional study was performed in 2013 on 185 patients in Iran. Data were selected through convenient sampling. The collected data included demographic variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…On the other hand, self-management behaviours are influenced by sociodemographic variables, health status and disease. 69 This may lead to some components not having the same applicability between different contexts or countries. The multiform way of offering these interventions also makes it difficult to analyse their individual effectiveness because most of them are centred in hospitals, which is distorted by the very concept of self-management interventions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, self-management behaviours are influenced by sociodemographic variables, health status and disease. 69 This may lead to some components not having the same applicability between different contexts or countries. The multiform way of offering these interventions also makes it difficult to analyse their individual effectiveness because most of them are centred in hospitals, which is distorted by the very concept of self-management interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we reported the development and psychometric properties of the SCBS (Additional file 1: Table S1) to assess self-care behaviors among patients with RA. Despite the importance of self-care behaviors among RA patients [22, 29, 30, 3234], there is a scarcity in the valid and reliable instruments to be applied for investigating the behaviors during health promotion interventions among RA patients. Although the initial version of the scale was developed in a previous study [26], psychometric properties of the scale were still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for not talking about pain lend insights into the need for health care providers to understand the need to educate patients on how to improve the communication of their pain experience to providers, friends, and family (Chaleshgar Kordasiabi et al, 2015; Wysocka-Skurska et al, 2016). Patients attempting to ignore their pain as a means of resolving it may most benefit from learning more effective techniques to communicate their pain and then may learn how to better manage their pain; a further important outcome may be that they are then offered more effective analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a significant burden on the population worldwide (McDougall, Hurd, & Barnabe, 2016). As a chronic inflammatory condition with no clear etiology, RA is known for its physical and psychosocial correlates of pain (Chaleshgar Kordasiabi et al, 2015), but there is scant information as to what motivates individuals to share their pain experiences with providers or what complementary health approaches individuals use to treat their pain. Treatment of the RA disease process, which is characterized by remissions and exacerbations (Dickens, McGowan, Clark-Carter, & Creed, 2002), aimed at reducing the symptoms associated with the systemic effects, modifying the disease process (Noack, Ndongo-Thiam, & Miossec, 2016), and reducing disability.…”
Section: Introductionmentioning
confidence: 99%